Bacteraemia in Intensive Care Unit: Clinical, Bacteriological, and Prognostic Prospective Study - Zineb Lachhab; Mohammed Frikh; Adil Maleb; Jalal Kasouati; Nouafal Doghmi; Yassine Ben Lahlou; Bouchra Belefquih; Abdelhay Lemnouer; Mostafa Elouennass (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objectives. We conducted a one-year observational study from December 2012 to November 2013 to describe the epidemiology of bacteraemia in intensive care units (ICU) of Mohammed V Military Teaching Hospital of Rabat (Morocco). Methods. The study consisted of monitoring all blood cultures coming from intensive care units and studying the bacteriological profile of positive blood cultures as well as their clinical significance. Results. During this period, a total of 46 episodes of bacteraemia occurred, which corresponds to a rate of 15,4/1000 patients. The rate of nosocomial infections was 97% versus 3% for community infections. The most common source of bacteraemia was the lungs in 33%, but no source was identified in 52% of the episodes. Gram negative organisms were isolated in 83,6% of the cases with Acinetobacter baumannii being the most frequent. Antibiotic resistance was very high with 42,5% of extended-spectrum beta-lactamases (ESBLs) in Enterobacteriaceae and 100% of carbapenemase in Acinetobacter baumannii. The antibiotherapy introduced in the first 24 hours was adequate in 72% of the cases. Conclusions. Bloodstream infections in ICU occur most often in patients over 55 years, with hypertension and diabetes. The bacteria involved are mainly Gram negative bacteria multiresistant to antibiotics. Early administration of antibiotics significantly reduces patients mortality.